FRI0072 Predictors of response to anti-TNF therapy in ra patients with moderate disease activity compared to those with high disease activity according to DAS28 scores'. (23rd January 2014) - Atzeni, F.; Marchesoni, A.; Filippini, M.; Caporali, R.; Gorla, R.; Cavagna, L.; Favalli, E.; Monti, G.; Sarzi-Puttini, P.
Abstract : Background: Studies have found that patients who start anti-TNF therapy with lower DAS28 scores are more likely to achieve disease remission (defined using a DAS28 <2.6). However no studies have previously evaluated predictors of response in RA patients with moderate disease activity (MDA) (DAS28 >3.2–5.1) compared to those with high disease activity (HDA) (DAS28 >5.1). Objectives: The aim of this study was to identify the clinical factors that predicted a good clinical response to anti-TNF in RA patients who had been divided into two groups according to baseline DAS28 scores (moderate: >3.2–5.1 and high: >5.1) and entered into the Lombardy Rheumatology Network (LORHEN) registry after five years of treatment with anti-TNF agents. Methods: We entered into the study all patients with no previous exposure to biologic agents who were starting one of the three available anti-TNF agents (ETN, IFN or ADa), and who had been both included in the LORHEN register and followed-up for a minimum of twelve months by 1999. The prospective protocol included information on demographics, the clinical characteristics of the patients and response measures. Disease activity at baseline and after 12 six months was assessed using the DAS28, and response was evaluated according to the EULAR improvement criteria. Potential predictors of response were identified using multivariate binary logistic regression models. Results: The study involved 1300 patients with established RA (326 ETA, 385 ADA, 589 INF), of whom 975 with high, and 325 with moderate, clinical activity were included in the analysis of clinical efficacy. At the start of therapy, patients had a mean age of 54.66±13.74 years, a disease duration of 7.49±7.88 years, and a baseline DAS-28 of 5.77±1.05 (HDA 6.23±0.71 vs. MDA 4.37±0.51, respectively). After a mean of twelve months, 21.39% of the patients had achieved a DAS-28 of ≤2.6 (HDA 16.17% vs. MDA 37.3%; P=0.0001) and were considered to be in remission. A total of 324 had achieved a good EULAR response (HDA 203 vs. MDA 121). A higher probability for good EULAR response in patients with HDA was associated with male gender (F vs M - OR 0.42, 95% CI 0.27-0.63; p:0.0001), a low baseline erythrocyte sedimentation rate (ESR) (OR 0.99, 95% CI 0.98-1.00; p:0.03), or an absence of comorbidities (OR 2.15, 95% CI 1.52-3.04 p:0.0001); in patients with MDA this was associated with no corticosteroids having been used (OR 2.06, 95% CI 1.12-3.77; p:0.02) and with male gender (F vs M - OR 0.48, 95% CI 0.27-0.85; p:0.01).Age, disease duration, RF and previous use of DMARDs did not predict response in this cohort of patients, but patients with HDA without concomitant comorbidities were more likely to achieve a good clinical response. Male gender was associated with a good EULAR response in both subgroups. Conclusions: We found that the percentage of patients with long-standing RA and MDA treated with anti-TNF agents who achieved remission as outpatients in the community was higher than those with HDA. Furthermore, those factors that predicted good EULAR were different in patients with MDA compared to those with HDA, with the exception of male gender. Disclosure of Interest: None Declared